Paediatric cardio-oncology: epidemiology, screening, prevention, and treatment. Issue 5 (7th March 2019) - Chow, Eric J; Leger, Kasey J; Bhatt, Neel S; Mulrooney, Daniel A; Ross, Colin J; Aggarwal, Sanjeev; Bansal, Neha; Ehrhardt, Matthew J; Armenian, Saro H; Scott, Jessica M; Hong, Borah
Abstract: With 5-year survival of children with cancer exceeding 80% in developed countries, premature cardiovascular disease is now a major cause of early morbidity and mortality. In addition to the acute and chronic cardiotoxic effects of anthracyclines, related chemotherapeutics, and radiation, a growing number of new molecular targeted agents may also have detrimental effects on the cardiovascular system. Survivors of childhood cancer also may have earlier development of conventional cardiovascular risk factors such as hypertension, dyslipidaemia, and diabetes, which further increase their risk of serious cardiovascular disease. This review will examine the epidemiology of acute and chronic cardiotoxicity relevant to paediatric cancer patients, including genetic risk factors. We will also provide an overview of current screening recommendations, including the evidence regarding both imaging (e.g. echocardiography and magnetic resonance imaging) and blood-based biomarkers. Various primary and secondary prevention strategies will also be discussed, primarily in relation to anthracycline-related cardiomyopathy. Finally, we review the available evidence related to the management of systolic and diastolic dysfunction in paediatric cancer patients and childhood cancer survivors.